Securing e-Health application of cloud computing using hyperchaotic image encryption framework. (May 2022) - R, Anandkumar; K, Dinesh; Obaid, Ahmed J.; Malik, Praveen; Sharma, Rohit; Dumka, Ankur; Singh, Rajesh; Khatak, Satish
Highlights: An integrated image encryption framework for securing e-Health application. Included an integrated way for attaining maximum resistance against vulnerable attacks. Incorporated reliable and potential diffusion process. Strengthen the chaotic map with respect to processing time, specificity and sensitivity. Abstract: Electronic health (e-Health) is one the latest technology that optimizes its societal benefits by implementing it in a cloud-based environment. However, the complete utilization of cloud-based e-Health facility is determined to be hampered by the challenges of security. Further, most of the data stored and transmitted as images are related to sensitive information of the patients. In this paper, a secure framework integrating e-Health and cloud using Hyper Chaos-based Image Encryption is proposed for potential implementation of security over sensitive image data transmitted over the clouds. This framework alternatively applies any one of the proposed chaos-based image encryptions and image scrambling schemes depending on the intensity and type of attack over the images shared in the cloud environment. Simulation experiments of the proposed framework are conducted to evaluate its potential in resisting known and unknown attacks that are possible under e-Health image sharing process. Graphical abstract: Image, graphical abstract .